First records of Tachydromia Meigen and Tachypeza Meigen (Diptera: Hybotidae) from Viet Nam, with descriptions of four new species - Grootaert, Patrick; Shamshev, Igor (Zootaxa, 2009)
First records of Tachydromia Meigen and Tachypeza Meigen from Viet Nam are provided, including descriptions of four new species: Tachydromia achterbergi sp. nov., Tachydromia annamensis sp. nov., Tachypeza vietnamensis sp. nov. and Tachypeza vriesi sp. nov. Tachydromia doi Shamshev & Grootaert is recorded for the first time from Viet Nam as well as a female of a new but unnamed Tachydromia. A key to Oriental species for both Tachydromia and Tachypeza is compiled.